Small Wind Turbine - Sharul Shafiq Bin Abd Aziz, Sharul Shafiq (2010)
This system focuses on the usage of electricity at home. Basically, it demonstrates how the electricity can be generated using motor. The implementation of this system is to realize the people especially in the matter of increasing electricity bill per year. This is because the electricity is getting more and more costly and is huge burden to the environment.